EVALUASI KESESUAIAN LAHAN GAMBUT UNTUK TANAMAN SENGON (Paraserianthes falcataria (L) Nielsen) DI DESA KUALA DUA KECAMATAN SUNGAI RAYA KABUPATEN KUBU RAYA - Nugraha, Gunawan; Herawatiningsih, Ratna; Nugroho R, Joko (JURNAL HUTAN LESTARI, 2013)
Plants Sengon (Paraserianthes falcataria (L) Nielsen) is one type of forest plants that are currently popular enough to be cultivated. Due to its rapid growth (fast growing) so that it can meet the market demand for timber. In addition to raw material for paper, timber plants can also be used as raw material container, wallboard, furniture, paper, and other crafts. This study aims to determine the limiting factor for crop suitability peatlands sengon (Paraserianthes falcataria (L) Nielsen) in the village of Kuala Dua Kecamatan Sungai Raya Kabupaten Kubu Raya. The benefits of the research are expected to be used as guidelines for the development sengon plants in the future especially in areas that serve as regional research and also expected to be an appropriate land management information.From the observations made ??in the field and laboratory analysis, and conduct an analysis of the suitability of the land, the land, including the location of the research into the actual land suitability level is not suitable (N) after the improvement of the quality of the actual land being the potential land suitability classes become marginally suitable (S3 ). Overall peatlands have been studied area of ??10 hectares belong to the class is not appropriate (N-ga). Limiting factors that cause incompatibility toughest peatland research the location for the plant is mature sengon fibric peat (g) and soil pH (a) low (3.49). Keyword : Evaluation, Suitability, Sengon, Peat